2003
DOI: 10.1146/annurev.nutr.23.011702.073212
|View full text |Cite
|
Sign up to set email alerts
|

DIETARY, EVOLUTIONARY, ANDMODERNIZINGINFLUENCES ON THEPREVALENCE OFTYPE2 DIABETES

Abstract: An evolutionary perspective is used to elucidate the etiology of the current epidemic of type 2 diabetes estimated at 151 million people. Our primate legacy, fossil hominid, and hunting-gathering lifestyles selected for adaptive metabolically thrifty genotypes and phenotypes are rendered deleterious through modern lifestyles that increase energy input and reduce output. The processes of modernization or globalization include the availability and abundance of calorically dense/low-fiber/high-glycemic foods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 156 publications
3
59
0
4
Order By: Relevance
“…The authors speculated that the observed increase in CVD risk observed in South Asian countries could be attributed to the effects of increasing urbanization on CVD risk factors [5]. The nutritional consequences of migrating from a low-income country to the US are similar to the nutritional consequences of migrating from a rural lifestyle to an urban lifestyle and similar to the effects of ''modernization'' in developing countries [19][20][21]. These consequences include increases reported for various nutrition-related CVD risk factors, including increased intake of saturated fats (i.e., animal foods), refined carbohydrates, sodium and decreased intake of dietary fiber and potassium [5].…”
Section: Introductionmentioning
confidence: 99%
“…The authors speculated that the observed increase in CVD risk observed in South Asian countries could be attributed to the effects of increasing urbanization on CVD risk factors [5]. The nutritional consequences of migrating from a low-income country to the US are similar to the nutritional consequences of migrating from a rural lifestyle to an urban lifestyle and similar to the effects of ''modernization'' in developing countries [19][20][21]. These consequences include increases reported for various nutrition-related CVD risk factors, including increased intake of saturated fats (i.e., animal foods), refined carbohydrates, sodium and decreased intake of dietary fiber and potassium [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that diabetes prevalence is increased because of modern lifestyles, urbanization, and economic development [1]. It is a global problem with devastating human, social, and economic impact, affecting around 300 million people worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…Following its rapidly increasing incidence worldwide over the past decades, type 2 diabetes has reached epidemic proportions with major health consequences at an individual as well as a public health level [2]. Major environmental features of relevance to the development of type 2 diabetes are chronic overnutrition and a sedentary lifestyle against a background of genetic predisposition [3]. Lifestyle intervention programmes offer the possibility to delay or even prevent the onset of type 2 diabetes [4].…”
Section: Introductionmentioning
confidence: 99%